Analisis Kinerja Keuangan Pada PT. Asuransi Umum Bumiputera Muda 1967 Cabang Bengkulu - Kamelia Kamelia; Sulisti Afriani (Universitas Malahayati, 2017)
Insurance is a financial institution that aims to provide protection against financial losses,caused by unforeseen events. To view the financial performance of a company, we can find outthrough the financial statements consisting of balance sheet and income statement and cash flowstatement.The purpose of this study was to determine whether the financial health of PT. AsuransiUmum Bumiputera Muda 1967 Bengkulu Branch. The analytical tool used in this research is to usethe solvency ratio, loss ratio, liquidity ratio and own retention ratio.The result showed that thefinancial condition of PT. Asuransi Umum Bumiputera Muda 1967 Bengkulu Branch is healthy. Byresults of 2013 the solvency ratio amounted to 121%, 124.64% in 2014 and 2015 amounted to122.5%. The loss ratio in 2013 amounted to 38.4%, amounting to 29.95% in 2014 and 2015 amountedto 76.87%. Liquidity ratio in 2013 amounted to 268.9%, amounting to 368.9% in 2014 and 2015amounted to 323.8%. Own retention ratio in 2013 amounted to 99.34%, amounting to 99.58% in 2014and 2015 amounted to 99.64%.